2022
DOI: 10.3389/fonc.2021.778185
|View full text |Cite
|
Sign up to set email alerts
|

Camrelizumab-Related Myocarditis and Myositis With Myasthenia Gravis: A Case Report and Literature Review

Abstract: Immune checkpoint inhibitors (ICIs) have substantially changed the treatment of a variety of malignant tumors. With the increasing of their usage, the unique immune-mediated toxicity profile of ICIs has become apparent. We report a case of esophageal squamous cell carcinoma in a patient who received anti-programmed cell death protein 1 (PD-1) (camrelizumab) therapy and the occurrence of sequential immune-related adverse events (irAEs). Although many irAEs have been reported, severe myositis caused by camrelizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Furthermore, in retrospective case-control study researchers found neuromuscular decompensation to be more pronounced in patients with anti–PD-1 treatment ( 47 ). It has been more previously reported that patients with a history of MG or positive anti-AChR antibody presented a myasthenic crisis after ICI treatment ( 48 51 ) compared with patients without a history of MG. For patients with a history of MG, the use of ICIs might activate the T-cell autoimmune response and may induce MG. For acetylcholine receptor antibody-positive MG patients, high doses of corticosteroids alone can exasperate the myasthenic crisis, and ASCO guideline recommend high doses of corticosteroids combined with gamma globulin or plasma replacement as first-line treatment ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in retrospective case-control study researchers found neuromuscular decompensation to be more pronounced in patients with anti–PD-1 treatment ( 47 ). It has been more previously reported that patients with a history of MG or positive anti-AChR antibody presented a myasthenic crisis after ICI treatment ( 48 51 ) compared with patients without a history of MG. For patients with a history of MG, the use of ICIs might activate the T-cell autoimmune response and may induce MG. For acetylcholine receptor antibody-positive MG patients, high doses of corticosteroids alone can exasperate the myasthenic crisis, and ASCO guideline recommend high doses of corticosteroids combined with gamma globulin or plasma replacement as first-line treatment ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses investigating the role of ICIs in irAEs have been published (9,(14)(15)(16)(17)(18)(19)(20)(21). Past case reports and narrative reviews have also summarized the literature describing an association of ICIs with MG (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). However, to the best of our knowledge, a rigorous analysis of the relationship between ICIs and both MG and LEMS has not been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, immune checkpoint inhibitors (ICIs) have shown considerable potential due to reports of their impressive efficacy in the field of oncotherapy (1), which has resulted in the development of radical novel strategies for treating various malignancies (2). Instead of killing tumour cells by direct exposure, ICIs function by regulating the behaviour of immune cells, such as T-cells (3).…”
Section: Introductionmentioning
confidence: 99%